TOLERANSI MASYARAKAT MINANGKABAU TERHADAP PERAN PEREMPUAN DALAM AKTIVITAS SENI BUDAYA - Efrida Efrida (Gelar : Jurnal Seni Budaya, 2009)
Women, in one hand, have a respected position in the matrilineal culture of Minangkabau society and, on the other hand, they are restricted when they want to express themselves in performing art. The efforts made by the female to demand that the Minangkabau society should tolerate women taking part in performing art, especially dancing, cause the pros and cons. However, the choreographers like Huriah Adam, Gusmiati Suid, Syofyani Bustamam, and Ery Mefry help the female gain wider access to take part in Minangkabau performing art. Key words : tolerance, women’s role, art